PENGGUNAAN INSTRUMEN PENILAIAN AFEKTIF DALAM PEMBELAJARAN PAI DI SMAN 1 YOGYAKARTA - Diah Arum Ratnawati; Sri Sumarni (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2013)
The background of this research is the emergence of problems in general about the ignorance of teachers PAI affective assessment instruments in schools, even in schools that in fact madrasah. However, there is a teacher at SMAN 1 Yogyakarta PAI that besides knowing affective assessment instruments also developed the use of affective assessment instruments. Teachers PAI also showed readiness to make lesson plans by attaching affective assessment instruments. Based on this study aims to determine the shape of affective assessment instruments and their use, as well as scoring and assessment results from the use of assessment instruments PAI affective learning in the school.This research is qualitative. Data was collected through interviews and documentation techniques. Examination of the validity of the data is done by holding the data triangulation.The results showed that: 1) Form of assessment instruments PAI affective learning in SMAN 1 Yogyakarta include: assessment of noble character and personality, instantly records, statements of honesty, self-assessment implementation IMTAQ in life, and mentoring questionnaire; 2) The use of assessment instruments for moral values and personality by observing the students, notes for the record by chance instantaneous behavior of the student and the actions/solutions provided, honesty statement given at UTS to develop an attitude scale instruments, implementation of self assessment IMTAQ in life filled by students and known by the by modifying old techniques Likert scale attitude, mentoring questionnaire given to the students of class X when he first dimentoring by Rohis the school by developing a questionnaire technique. 3) given scoring is always = 5, often = 4, 3 = rarely, never = 1, while the final assessment by using the formula NA = ( 2A + B + 2C ) / 5, where A is the liability aspect, B aspect and C is a plus aspect of noble character who do.